Groups satisfying the condition of weak minimality for subgroups of derived length two - Onishchuk, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We consider non-Abelian solvable and radical groups that satisfy the condition of weak minimality for subgroups of derived length two. We show that these groups are minimax groups. This is not true for locally solvable groups. We give an example of a group of derived length three that satisfies the condition of weak minimality for the indicated subgroups but is not a minimax group.